THU0072 Comparison of Characteristics of Ankylosing Spondylitis in Association with Familial Mediterranean Fever with Those of Typical Ankylosing Spondylitis. (10th June 2014) - Solmaz, D.; Akar, S.; Kisacik, B.; Apras, S.; Senel, S.; Onat, A.M.; Kasifoglu, T.; Aksu, K.; Sari, I.; Ozturk, M.A.; Sayarlioglu, M.; Akdogan, A.; et al.
Abstract : Background: Several case reports and a few published studies suggest a link between Familial Mediterranean Fever (FMF) and ankylosing spondylitis (AS). There is very limited data on the clinical features of AS that develops in patients with FMF. Objectives: To compare the demographic and clinical features of patients with AS in association with FMF to patients with AS alone. Methods: 73 patients with AS in co-existence with FMF (AS-FMF) who have been followed at 8 different hospitals were compared to 81 consecutive patients with AS alone. All of the patients fulfilled the modified New York criteria for AS and the patients with FMF additionally met the Livneh criteria for FMF. Patients demographic and clinical data were extracted from patients' charts; MEFV genotypes, HLA B27 status and C reactive protein levels and radiographic results were also recorded if available. Results: Patients in the AS-FMF group were younger and had a shorter disease duration. Gender distribution and age of onset of AS were similar in both groups; but diagnostic delay was longer and family history (for SpA) was reported more frequently in the AS group. Peripheral arthritis and heel enthesitis were more prevalent among AS-FMF patients whereas a higher proportion of patients in the AS group had HLA-B27 and had radiologic evidence of spinal involvement (Table). M694V allelic variation was detected in 78.7% of the patients with FMF and AS. Conclusions: Clinical characteristics of AS in association with FMF may show some differences from typical AS, such as less spinal involvement. Relatively high prevalence of M694V variant among patients with FMF in coexistence with AS compared to that reported in historic cohorts of Turkish FMF patients as well as lower prevalence of HLA-B27 compared to that in AS patients may suggest that such genetic differences may also be accounted for some of the differences between the patients with AS in association with FMF and the typical AS patients. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4575